Cam Femoroacetabular Impingement as a Possible Explanation of Recalcitrant Anterior Knee Pain - Vicente Sanchis-Alfonso; Marc Tey; Joan Carles Monllau (Case Reports in Orthopedics)
We present a case of a patient with chronic anterior knee pain (AKP) recalcitrant to conservative treatment who returned to our office for severe hip pain secondary to Cam femoroacetabular impingement (Cam FAI) at 10 months after the onset of knee pain. This case highlights the fact that the main problem is not in the patella but in the hip in some patients with AKP. We hypothesize that there is an external femoral rotation in order to avoid the impingement and therefore the hip pain in patients with Cam FAI. This functional femoral rotation could provoke a patellofemoral imbalance that may be, in theory, responsible for patellofemoral pain in this particular patient. In our case, Cam FAI resolution was related to the resolution of AKP.